Non-templated ambient nanoperforation of graphene: a novel scalable process and its exploitation for energy and environmental applications - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (Nanoscale, 2015)
Nano-perforation of 2D graphene sheets is a recent and strategically significant means to exploit such materials in modern applications such as energy production and storage. However, current options for the synthesis of holey graphene (hG) through nano-perforation of graphene involve industrially undesirable steps viz., usage of expensive/noble metal or silica nanoparticle templates and/or hazardous chemicals. This severely hampers its scope for large scale production and further exploitation. Herein, we report for the first time a scalable non-templated route to produce hG at ambient conditions. Nano-perforation is achieved with tunable pore size via the simple few layer co-assembly of silicate-surfactant admicelles along the surface of graphene oxide. A gentle alkali treatment and a reduction at optimized conditions readily yielded holey graphene with a remarkable capacitance (similar to 250 F g(-1)) and interesting adsorption abilities for pollutants. Density functional theory based computational studies reveal interesting insights on the template free nano-perforation at a molecular level. This simple rapid process not only excludes the need for expensive templates and harmful chemicals to yield hG at attractively ambient, chemically placid and industrially safer conditions, but also creates no hurdles in terms of scaling up.

Redox-mediated 3D graphene based nanoscoop design for ultracapacitor applications - Rani, Pallavi; Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (New Journal of Chemistry, 2017)
Contemporary energy storage devices significantly rely on the rational design of micro and nanostructural features of electrode materials for efficient ion transport. A judicious concept of utilizing the extended charge mobility on the third dimension along with an active redox couple to significantly maximize the capacitance has been demonstrated via (a) the fabrication of a 3D network from 2D graphene and (b) the introduction of an active redox species. Compared with traditional graphene systems, an unprecedented 8-fold gain of capacitance that was sustained with minimal loss even beyond 5000 cycles is achieved and is reported for the first time. This was due to the complementary advantage of both the electric double layer capacitance of the 3D graphene electrode and the redoxmediated pseudocapacitance of K3Fe(CN)(6) in alkaline electrolytes. Colloidal polystyrene spheres with a tunable size range were used as sacrificial templates for generating the 3D network. This design outperforms others, is an excellent candidate as an ultracapacitor and is envisaged to lead to new opportunities in several electrochemical applications.

Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres

Molecularly engineered graphene oxide anchored metal organic assembly: an active site economic bi-functional electrocatalyst - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (FlatChem, 2021)
Low-temperature fuel cells are the most promising sustainable energy technology as they use hydrogen, an environmentally clean fuel. However, the sluggish kinetics of oxygen electrochemistry, a chronic issue, is holding them from commercialization. Herein, we address this issue through a molecular level design of a Graphene oxide anchored Metal Organic Molecular Assembly (G-MOMA) based catalyst. This non-precious metal catalyst consists of Ni and Fe ions ligated by graphene oxide supported terpyridine, a unique molecular assembly design that maximizes the utilization of active metal centers. This G-MOMA catalyst brings down an over potential (240 mV) for oxygen evolution reaction (OER) as close as that of the bench mark catalyst Ru/C with an impressive Tafel slope of 58 mV/dec and a cyclic stability of >30,000 cycles. G-MOMA excels in oxygen reduction reaction (ORR) too with an onset at 0.88 V (vs RHE). The remarkably stable G-MOMA catalyst surprises with an excellent bi-functionality towards both OER and ORR with an overall potential difference of mere 0.77 V, which is 180 mV and 70 mV lesser than the standard Pt/C and Ru/C catalysts, respectively. The G-MOMA catalyst is well in the activity range of the state-of-art bi-functional catalysts and yet cheaper by many folds.
Keywords: Bi-functional electrocatalyst; graphene oxide; Metal organic molecular assembly; Oxygen Evolution Reaction; oxygen reduction reaction; terpyridine